The Influence of Women's Employment in Indonesia - Cindy Alfina Damayanti; Muhammad Anas (Universitas KH. Abdul Chalim Mojokerto, 2026)
Gender equality is important in efforts to reduce poverty because it can increase women's access to education, employment, and economic opportunities. However, current conditions show that women's labor participation is still lower than that of men, reflecting gender inequality in the labor market. This study aims to estimate the direction and magnitude of the influence of the average wages of formal and informal sector workers, the open unemployment rate (TPT), the number of female workers, the average length of female schooling, and women's productivity on the percentage of poor people in each province in Indonesia in 2020–2024 by regressing the data of the Random Effects Model panel(REM). The regression results showed that the average wages of informal sector workers and the average length of female schooling had a negative effect on poverty rates, while the open unemployment rate (TPT), the number of female workers, and women's productivity had a positive effect on poverty. Then, the average wages of formal sector workers have no effect on the percentage of the poor. The government needs to pay attention to the quality of education and skills of the workforce in order to be able to compete in an increasingly competitive job market. In addition, the quality of work needs to be improved through the provision of decent, stable, and social security jobs so that their contribution to improving welfare can be more optimal.